2019
DOI: 10.1021/acs.energyfuels.9b02869
|View full text |Cite
|
Sign up to set email alerts
|

Condensational Growth of Fine SiO2 Particles by Magnetized Wetting Agent Tween-20 Solution Vapor

Abstract: The emission of fine particles from coal-fired power plants causing environmental and human health issues is a topic of concern. The enlargement of particles seems to be a promising pretreatment technology for fine particles removal with traditional electrostatic precipitator. The effects of magnetized Tween-20 solution (MTS) by heterogeneous condensation for particle growth were carried out based on the growth tube. The experimental results indicate that the particle growth is more favored by MTS compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Recently, in terms of the heterogeneous condensation mechanism, Xu et al used an environmental scanning electron microscopy system to directly visualize the heterogeneous condensation process on insoluble particle surfaces and found that the Fletcher theoretical critical supersaturation was higher than that experimentally measured. Xiong et al proposed a heterogeneous nucleation model based on the Fletcher classical nucleation theory and molecular kinematics theory, considering the effect of surface diffusion mechanism of water vapor molecules, line tension, and roughness . Yin et al, Yu et al, Natale et al, Tammaro et al, and Wang et al conducted several experiments on the heterogeneous condensation of different particles in a growth tube and analyzed the effect of gas or vapor temperature, particle concentration, gas composition, wetting agent, and magnetic field. Zhang et al discussed the influence of the particle size, chemical composition, and mass fraction of components on the heterogeneous nucleation critical condition based on the classical Köhler theory …”
Section: Introductionmentioning
confidence: 99%
“…Recently, in terms of the heterogeneous condensation mechanism, Xu et al used an environmental scanning electron microscopy system to directly visualize the heterogeneous condensation process on insoluble particle surfaces and found that the Fletcher theoretical critical supersaturation was higher than that experimentally measured. Xiong et al proposed a heterogeneous nucleation model based on the Fletcher classical nucleation theory and molecular kinematics theory, considering the effect of surface diffusion mechanism of water vapor molecules, line tension, and roughness . Yin et al, Yu et al, Natale et al, Tammaro et al, and Wang et al conducted several experiments on the heterogeneous condensation of different particles in a growth tube and analyzed the effect of gas or vapor temperature, particle concentration, gas composition, wetting agent, and magnetic field. Zhang et al discussed the influence of the particle size, chemical composition, and mass fraction of components on the heterogeneous nucleation critical condition based on the classical Köhler theory …”
Section: Introductionmentioning
confidence: 99%